Systematic Review of School‐Based Interventions to Modify Dietary Behavior: Does Intervention Intensity Impact Effectiveness?. (June 2016) - Racey, Megan; O'Brien, Charlene; Douglas, Sabrina; Marquez, Olivia; Hendrie, Gilly; Newton, Genevieve
ABSTRACT: BACKGROUND: Owing to the associations between diet and health, it is important that effective health promotion strategies establish healthful eating behaviors from an early age. We reviewed the intensity of school‐based interventions aimed to modify dietary behavior in preadolescent and adolescents and related intervention characteristics to effectiveness. METHODS: Our systematic literature search of 8 databases sought to identify interventions measuring dietary intake in school settings to students aged 9 to 18. We evaluated these studies for effectiveness, intensity, intervention category, and follow‐up measures. RESULTS: Of the 105 interventions 81 were found to be effective immediately postintervention, irrespective of intensity. Studies that were 6 weeks to 5 months in duration, targeted students' environment or group (alone or in combination), and reached students only in schools were more effective. Only one‐fifth of interventions conducted a follow‐up measure, and a majority showed a loss of effectiveness from postintervention to follow‐up. CONCLUSIONS: We identified characteristics of effective interventions. These findings may inform the development of future interventions targeting dietary behavior in preadolescents and adolescents in the school‐based setting.